Investigating the Effect of Flood Sedimentation on Vegetation and Topsoil Changes in Abdalan Plain - Esfandia Jahantab; Mohsen Farzin; Majid Khazaei (مدیریت بیابان, 2021)
The purpose of this study is to investigate the effect of floodwater spreading on the vegetation of Abdalan plain after 24 years since the implementation of the project. For this purpose, the changes in vegetation density and diversity and soil characteristics of the floodwater spreading were considered as the basis for the effectiveness of various floods. To determine the characteristics of density and percentage of vegetation, percentage of rocks, gravels, litter, and bare soil as well as Physico-chemical characteristics of soil in each area of floodwater spreading and control, 3 transects with a length of 100 meters were deployed. Measuring and sampling were performed on one square meter plots. The results of field studies led to the identification of 36 plant species and 33 genera belonging to 14 plant families. The most important plant families in the region are Asteraceae, Poaceae, and Fabaceae. The results showed that there are 34 plant species in the floodwater spreading area and 25 plant species in the control area. Of these, 12 plant species were observed only in the floodwater spreading area and 2 plant species were observed only in the control area, and 23 plant species were common in both areas. According to the results, the percentage of cover and density of plants in the floodwater spreading area has increased compared to the control area by 32.8% and 4.4%, respectively. The percentage of clay, silt, and sand has increased compared to the control in the field of floodwater spreading. Sufficient moisture and suitable fine-grained sediments to maintain the required moisture for a longer time as well as the seeds in the sediments have caused the growth and increase of density and canopy cover of plants in the field of floodwater spreading. These operations on the Abdalan plain have caused the revitalization of the region by changing the physical characteristics of the surface soil and improving vegetation conditions.